(untitled) (Journal of Governance and Development (JGD), 2024)
This study examines the experiences of the selected communities in the National Task Force to End Local Communist Armed Conflict (NTF- ELCAC) Poverty Reduction, Livelihoods, and Employment Cluster of Executive Order No. 70. It utilized qualitative research through the phenomenology approach as it studied the experiences of the selected communities in Kibawe, Bukidnon. It employed thematic analysis in this investigation to assess the study’s focus group discussion. The study concludes that the whole-of-the-nation approach of the government was an effective tool for the government to uplift the living conditions of the selected communities by reducing poverty through livelihood and employment programs, penetrating the most insurgency-vulnerable areas in the municipality, and increasing the representation of the selected communities in the local government units through their representatives. These programs and projects under NTF-ELCAC PRLEC have had a political, social, and economic impact on the lives of the selected communities by reducing poverty, providing work opportunities for the communities, and helping them to become self-reliant without revolting against the government.